Inhibitory effects of three Philipine medicinal plants or somatic and germ cell genetocity - Geslani, Gemma P.
The clastogenic and anticlastogenic effects of the fruit concentrate of Momordica charantia Linn (ampalaya) family Cucurbitaceae, fruit concentrate of Averrhoa bilimbi Linn (kamias) family Oxalidaceae and decoction from drief stems of Tinospora rumphii Boerl. (Makabuhay) fami;ly Menisperamceae on mammalian somatic cells were determined using the micronucleus test. Three dose levels per sample were orally given to test animals by use of a gavage. Dimethylnitrosamine and tetracycline hydrochloride, two known mutagens, were used as positive controls and were administered by intraperitoneal injection. The three plant preparations, at all dosages, were proven not to possess chromosome-breaking properties as evidenced by low micronuclei counts. Instead, they were found to inhibit the chromose-damaging potential of the two mutagens. The dominant lethal assay was employed to measure mutagenic and antimutagenic effects of the test systems on germ cells. For this test, only one dose per plant sample was used and the only positive control utilized was tetracycline. Routes of administration of mutagen and sample were the same as in the micronucleus test. M. charantia, A. bilimbi and T. rumphii were all found to be non-mutagenic to germ cells. There were no significant differences in the different indices used, with respect to the control group. Howeverm varied responses to the three plant systems were observed. With M.charantia ande A. bilimbi the fertility index and gestation index were increased and percent dead implants was lowered while with T. rumphii only the fertility index was altered.
Theses--(Master in Science in Biochemistry) UPCM
Keywords: Plants, Medicinal